c-Src regulates the simultaneous rearrangement of actin cytoskeleton, p190RhoGAP, and p120RasGAP following epidermal growth factor stimulation (The Rockefeller University Press, 1995)
Analysis of C3H10T1/2 murine fibroblasts overexpressing wild type and dominant negative variants of c-Src has demonstrated a requirement for c-Src in EGF-induced mitogenesis. Correlating with the ability of c-Src variants to potentiate or inhibit EGF-dependent DNA synthesis is the phosphotyrosine content of multiple cellular proteins, including p190- RhoGAP, a protein thought to regulate growth factor-induced actin cytoskeleton remodeling by modulating the activity of the small GTP binding protein, Rho. Because the in vivo phosphotyrosine content of p190 varies with the level of active c-Src and not with EGF treatment, p190 is considered to be a preferred substrate of c-Src. To determine whether tyrosyl phosphorylation of p190 (by c-Src) could influence EGF- dependent actin remodeling, we used conventional and confocal immunofluorescence microscopy to examine the intracellular distribution of p190, actin, and p120RasGAP in EGF-stimulated or unstimulated 10T1/2 Neo control cells and cells that stably overexpress wild-type (K+) or kinase-defective (K-) c-Src. We found that in all cell lines, EGF induced a rapid and transient condensation of p190 and RasGAP into cytoplasmic, arclike structures. However, in K+ cells the rate of appearance and number of cells exhibiting arcs increased when compared with control cells. Conversely, K- cells exhibited delayed arc formation and a reduction in number of cells forming arcs. EGF-induced actin stress fiber disassembly and reassembly occurred with the same kinetics and frequency as did p190 and RasGAP rearrangements in all three cell lines. These results, together with the documented Rho-GAP activity intrinsic to p190 and the ability of Rho to modulate actin stress fiber formation, suggest that c-Src regulates EGF-dependent actin cytoskeleton reorganization through phosphorylation of p190.